Arithmetic algorithmic basis of computer modeling tools - Гамаюн, В. П. (Problems of Informatization and Control, 2008)
Proposed application of the principle of specialization to enhance the efficiency of computers and computer tools at the level of number systems . Specialized and problem-oriented notations make arithmetic algorithmic basis of computer modeling tools